2014
DOI: 10.1186/1476-511x-13-35
|View full text |Cite
|
Sign up to set email alerts
|

Impact of currently prescribed lipid-lowering drugs on plasma PCSK9 concentration: single or in combination study in rats

Abstract: BackgroundAn emerging data suggested a significant impact of statins on PCSK9 concentration, while the rapid impacts of other lipid-lowering drugs such as ezetimibe and xuezhikang alone or in combination on PCSK9 and lipid profile have not been assessed. This study aims to investigate whether an enhanced PCSK9 concentration by single or combined therapy of lipid-lowering drugs currently used precedes the changes of lipid profile in rats.MethodsSixty-three rats were randomly divided into six groups and orally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In an in vitro study by the same group, ezetimibe had no effect on PCSK9 protein secretion by HepG2 or Caco-2 cells [23]. In an animal study, 3-day ezetimibe consumption significantly increased control-related plasma PCSK9 concentration in rats before any lipid changes could be observed [24]. On the whole, the reason for these contradictory results extending from in vitro studies to clinical interventions remains open.…”
Section: Serum Marker Of Cholesterol Metabolismmentioning
confidence: 90%
“…In an in vitro study by the same group, ezetimibe had no effect on PCSK9 protein secretion by HepG2 or Caco-2 cells [23]. In an animal study, 3-day ezetimibe consumption significantly increased control-related plasma PCSK9 concentration in rats before any lipid changes could be observed [24]. On the whole, the reason for these contradictory results extending from in vitro studies to clinical interventions remains open.…”
Section: Serum Marker Of Cholesterol Metabolismmentioning
confidence: 90%
“…It has been proposed that the effect of fenofibrate on PCSK9 is indirect, rather than a direct effect on gene transcription as is observed with statins . There is some evidence from animal studies that ezetimibe upregulates the PCSK9 and LDLR genes; however, a previous study in humans did not find an effect of ezetimibe on PCSK9 . Increases in PCSK9 concentrations of 13% to 41% (versus placebo) have been reported after treatment with simvastatin or atorvastatin .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ezetimibe and fenofibrate on PCSK9 is unclear. Animal studies suggest that ezetimibe increases PCSK9 levels, but no effect was seen in humans . The change in PCSK9 levels with fibrates varies widely among reports …”
Section: Introductionmentioning
confidence: 99%
“…Ezetimibe, an inhibitor of intestine cholesterol absorption, can decrease cholesterol synthesis and reduce circulating LDL-C concentration whenever it is prescribed alone or in combination with statins in controlling dyslipidemia [ 24 , 25 ]. Recently, several researchers have described that ezetimibe or the combination of ezetimibe and statin stimulates the expression of PCSK9 [ 12 , 26 ]. A study from Davignon J et al reported that patients treated with statins alone had a 45% increase in PCSK9 levels and those treated with statin plus ezetimibe showed an approximately 77% increase in PCSK9 concentrations [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that ezetimibe induced a rapid increase of plasma PCSK9 concentration prior to the decrease of LDL-C levels in rats, even after 3 days of administration [ 12 ]. Hence, the aim of the present study was to investigate (1) the rapid impacts of ezetimibe on PCSK9 expression in different organs; (2) the underlying mechanisms for the elevated plasma PCSK9 levels after ezetimibe treatment using this 3-days’ rat model.…”
Section: Introductionmentioning
confidence: 99%